Fenomena Istri sebagai Pencari Nafkah Utama dalam Perspektif Mazhab Syafi’i - Muchamad Khoirul Umam; Hari Widiyanto; Ahmad Nursobah (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This phenomenon raises questions regarding the legal status of financial support (nafkah), the obligations of husbands and wives, and the legal implications when viewed through the lens of Shafi’i jurisprudence. The research employs a normative-juridical method with a library research approach, drawing on classical Shafi’i fiqh literature as well as secondary sources such as books, journals, and relevant articles. Data were analyzed descriptively and analytically by outlining normative provisions in Shafi’i jurisprudence and linking them to contemporary social realities. The findings reveal that, according to the Shafi’i school, the husband’s obligation to provide financial support does not lapse even if the wife works or assumes the role of the main breadwinner, as this obligation is a consequence of the marriage contract. Meanwhile, wives are permitted to work as long as they obtain their husband’s permission, adhere to Islamic legal guidelines, and do not neglect household responsibilities. Thus, the phenomenon of wives as primary breadwinners is permissible insofar as it is carried out within the framework of Islamic law as understood in the Shafi’i school.